Incidence and neighborhood-level determinants of child welfare involvement. (November 2020) - Lotspeich, Sarah C.; Jarrett, Ryan T.; Epstein, Richard A.; Shaffer, April M.; Gracey, Kathy; Cull, Michael J.; Raman, Rameela
Abstract: Background: Child maltreatment is a global public health issue that has been linked with multiple negative health and life outcomes. Objective: This study evaluates the association between children placed in out-of-home care and neighborhood-level factors using eight years of administrative data. Participants and setting: Between 2011–2018, 33, 890 unique instances of child welfare involvement were captured in a department of child and family services database in a southern state in the United States. Methods: Removal addresses were geocoded and linked to the U.S. Census Bureau's American Community Survey to obtain census tract socioeconomic factors. Incidence overall and stratified by individual and neighborhood-level factors was computed. Rate ratios, relative indexes of inequality, and concentration curves quantified disparities in incidence of child welfare involvement by neighborhood-level factors. Results: Incidence of children less than 19 years old placed into out-of-home care was 255 per 100, 000 person-years (95 % CI: 252, 258). At the individual level, incidence was highest among children <5 and 15–17 years old, comparable between male and female children, and higher among Black children. At the neighborhood level, incidence was highest in census tracts with lower median household incomes, higher percentages of households below poverty or of female-headed or single-parent households, higher unemployment rates, and fewer residents with some college education or health insurance. Conclusions: Incidence of children placed into out-of-home care is disproportionally higher for those who live in disadvantaged communities. Understanding neighborhood-level risk factors that may be linked to child welfare involvement can help inform policy and target prevention efforts.